Analisis Faktor - Faktor Yang Mempengaruhi Manajemen Laba Pada Perusahaan Consumer Cyclicals Dengan Ukuran Perusahaan Sebagai Variabel Moderasi Yang Terdaftar Di Bursa Efek Indonesia (BEI) Periode 2021 - 2022 - Chandra, Chandra; Jhonatan, Jerry; Khowen, Jesen Van (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2024)
This research aims to examine and analyze the factors that influence earnings management with company size as a moderator. These factors include tax planning, audit committee, independent commissioner, institutional ownership, managerial ownership, and profitability. This research uses Consumer Cyclicals companies listed on the IDX for the 2021 – 2022 period as the population. Sampling used the purposive sampling method. The total sample obtained was 102 Consumer Cyclicals companies. This research uses analysis techniques with the moderated regression method using SmartPLS version 3.2.9. The results of this research state that partially, tax planning, audit committee, independent commissioner, managerial ownership and profitability have no effect on earnings management, institutional ownership has a significant negative effect on earnings management. Institutional ownership influences earnings management. Institutional ownership is able to moderate the relationship between managerial ownership and earnings management. Institutional ownership is unable to moderate the relationship between tax planning, audit committee, independent commissioners, profitability and earnings management.